2013
DOI: 10.1002/hec.2991
|View full text |Cite
|
Sign up to set email alerts
|

Has Increased Body Weight Made Driving Safer?

Abstract: We develop a model of alcohol consumption that incorporates the negative biological relationship between body mass and inebriation conditional on total alcohol consumption. Our model predicts that the elasticity of inebriation with respect to weight is equal to the own-price elasticity of alcohol, consistent with body mass increasing the effective price of inebriation. Given that alcohol is generally considered price inelastic, this result implies that as individuals gain weight, they consume more alcohol but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Recent research on the relationship between obesity and motor vehicle fatalities has focused on the determinants of death or serious injury to drivers given the event of a motor vehicle crash. The consensus from this research is that obesity is associated with a greater risk of fatality in the event of a motor vehicle crash (see, in particular, Carter et al (2014), Desapriya et al (2014), Dunn and Tefft (2014), Jehle et al (2012), Joseph et al (2017 and Rice and Zhu (2013)). Although earlier research indicated that heavier drivers and passengers might be less at risk of dying once a crash has occurred because of the so-called cushion effect associated with the distribution of subcutaneous fat, more recent analyses have found little evidence in support of that hypothesis (Dunn and Tefft, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research on the relationship between obesity and motor vehicle fatalities has focused on the determinants of death or serious injury to drivers given the event of a motor vehicle crash. The consensus from this research is that obesity is associated with a greater risk of fatality in the event of a motor vehicle crash (see, in particular, Carter et al (2014), Desapriya et al (2014), Dunn and Tefft (2014), Jehle et al (2012), Joseph et al (2017 and Rice and Zhu (2013)). Although earlier research indicated that heavier drivers and passengers might be less at risk of dying once a crash has occurred because of the so-called cushion effect associated with the distribution of subcutaneous fat, more recent analyses have found little evidence in support of that hypothesis (Dunn and Tefft, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The consensus from this research is that obesity is associated with a greater risk of fatality in the event of a motor vehicle crash (see, in particular, Carter et al (2014), Desapriya et al (2014), Dunn and Tefft (2014), Jehle et al (2012), Joseph et al (2017 and Rice and Zhu (2013)). Although earlier research indicated that heavier drivers and passengers might be less at risk of dying once a crash has occurred because of the so-called cushion effect associated with the distribution of subcutaneous fat, more recent analyses have found little evidence in support of that hypothesis (Dunn and Tefft, 2014). The suggestion of a U-shaped pattern (lower BMI and very high BMI are associated with a greater risk of fatality) has been reported by a number of studies, and others find no statistical relationship between death rates or fatality risk and being overweight (as determined separately from obese) (Jehle, 2012;Zhu et al, 2006Zhu et al, , 2010Simmons and Zlatoper, 2010;Sivak et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation